Global research trends in consumer behavior and sustainability in e-commerce: A bibliometric analysis of the knowledge structure - Rita, P. (2022)
The adoption of blockchain technology by companies can change the way they interact with stakeholders, redeﬁning communication strategies and other marketing processes. In this study, we investigated the relevance of blockchain applications for marketing management from the perspective of marketing-related professionals. Answers about blockchain technology application in the marketing arena were collected from the social platform Quora. The data were analyzed through text mining and Spearman’s correlation coefﬁcient to assess the degree of association, inherent intensity, and the association signiﬁcance between the variables payments, supply chain, loyalty programs, digital marketing, credential management, and marketing management, using Quora- speciﬁc metrics, namely, upvotes, shares, and views. The results posit blockchain technology as being an asset for marketing, with greater relevance in supply chain and internal management among marketing operations. Professionals will be able to potentially improve internal management systems and marketing campaigns, which will enhance companies’ competitive advantage.